Legal Regulation of Marriage Relations with Foreign Citizens (on the Example of Vietnam) - V. R. Atnashev (Евразийская интеграция: экономика, право, политика, 2022)
The article discusses, first of all, some features of the Vietnamese legislation concerning marriages with foreign citizens and issues of citizenship. The problem of forced and fictitious marriages is also touched upon.Aim. Identification of specifics of the Vietnamese legislation on marriage and family and some topical problems in the field of mixed marriages.Tasks. Analysis of main provisions of the Law on Marriage and Family of Vietnam, the role of international treaties in this sphere, comparison of the situation with fictitious marriages in Vietnam and the Russian Federation.Methods. Comparative legal analysis of the norms of international private law in the field of marriage and family relations, description of the approaches of Vietnamese legislation to limping marriages and remission, as well as analysis of judicial practice in relation to fictitious marriages of Vietnamese citizens in the Russian Federation.Results. The Socialist Republic of Vietnam and the Russian Federation, representing different regions of the world and legal systems, have similar problems in the field of marriage and family relations involving foreign elements, which in Vietnam are exacerbated by social problems and weak protection of the rights of women and girls.Conclusion. The case of Vietnam demonstrates the conclusion of bilateral agreements and of universal conventions enhance eliminating the problem of conflict of law (limping marriages), while participation in international organizations improves the socio-economic situation of the population and develop mechanisms for protecting human rights in the field of marriage and family relations.